A volume-limited survey of mCP stars within 100 pc – I. Fundamental parameters and chemical abundances. Issue 2 (15th November 2018) - Sikora, J; Wade, G A; Power, J; Neiner, C
ABSTRACT: We present the first results of a volume-limited survey of main-sequence (MS) magnetic chemically peculiar (mCP) stars. The sample consists of all identified intermediate-mass MS stars (mCP and non-mCP) within a heliocentric distance of 100 pc as determined using Hipparcos parallaxes. The two populations are compared in order to determine the unique properties that allow a small fraction of MS stars with masses 1.4 M_ to host strong, large-scale magnetic fields. A total of 52 confirmed mCP stars are identified using published magnetic, spectroscopic, and photometric observations along with archived and newly obtained spectropolarimetric (Stokes V ) observations. We derive the fundamental parameters (effective temperatures, luminosities, masses, and evolutionary states) of the mCP and non-mCP populations using homogeneous analyses. A detailed analysis of the mCP stars is performed using the llmodels code, which allows observed spectral energy distributions to be modelled while incorporating chemical peculiarities and magnetic fields. The surface gravities and mean chemical abundances are derived by modelling averaged spectra using the gssp and zeeman spectral synthesis codes. Masses and stellar ages are derived using modern, densely calculated evolutionary model grids. We confirm a number of previously reported evolutionary properties associated with mCP stars including a conspicuously high incidence of middle-aged MS stars with respect to the non-mCP subsample; the incidence of mCP stars is found to sharply increase with mass from 0.3 per cent at 1.5 M_ to ≈11 per cent at 3.8 M_ . Finally, we identify clear trends in the mean photospheric chemical abundances with stellar age.